Eighteenth-century visions of the Stone Age - Liisa Kunnas-Pusa (Septentrio Academic Publishing, 2021)
Archaeological concepts of prehistory and the Stone Age are rooted in nineteenth-century scientific discoveries, which extended the human past much further back in time than was previously thought. Without this deep past, the disciplines of archaeology and history would not be what they are today. However, when the division of prehistory into the ages of stone, bronze, and iron was introduced in 1836, it was already an old idea. Stone Age artefacts and the initial phase of human history were discussed in the eighteenth-century academic world, even though the periodisation of history was constructed differently. In the philosophy of the Enlightenment several ideas surfaced which were essential to the formation of archaeology as a scientific practice, and which still affect the way the prehistoric past is imagined. This article examines the concept of a prehistoric, furthest past in Finnish scientific texts, within the framework of eighteenth-century Swedish traditions of science and historiography. How did the scholars in the Academy of Turku view Stone Age artefacts that had a multi-faceted nature in the antiquarian tradition? In what way did their visions of the earliest phase of the Nordic past set up later nationalistic narratives about prehistory?